1984
DOI: 10.1021/bi00312a023
|View full text |Cite
|
Sign up to set email alerts
|

Core expansion and electronic structure of the porphyrin in the neutral pH form of copper cytochrome c

Abstract: for model 4-, 5-, and 6-coordinate copper porphyrins show considerable destabilization of the a2u orbital caused by addition of a ir-donating axial ligand. Thus, the calculations support previous interpretations of spectral changes based on addition of an axial fifth ligand in the copper-modified heme proteins and copper porphyrins in coordinating solvents. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 46 publications
5
21
0
1
Order By: Relevance
“…According to this study, there is an electronic state whose energy is located below that of the Q band, which is mostly d(z 2) ~ d(x 2 -y2) but with appreciable CT a2u('rr)~ d(x 2 _y2) character. Thus, although previous calculations [2,3] stated that only the excited CT state can be sufficiently low in energy for 5-coordinate CuP and participates in excitation relaxation processes, this recent study [17] showed that the excited (d, d) state likely plays an important role in excitation deactivation, a conclusion which is consistent with the experimental data of our current and previous [4][5][6][7][8] studies of CuP.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…According to this study, there is an electronic state whose energy is located below that of the Q band, which is mostly d(z 2) ~ d(x 2 -y2) but with appreciable CT a2u('rr)~ d(x 2 _y2) character. Thus, although previous calculations [2,3] stated that only the excited CT state can be sufficiently low in energy for 5-coordinate CuP and participates in excitation relaxation processes, this recent study [17] showed that the excited (d, d) state likely plays an important role in excitation deactivation, a conclusion which is consistent with the experimental data of our current and previous [4][5][6][7][8] studies of CuP.…”
Section: Resultssupporting
confidence: 89%
“…As predicted by theoretical calculations [2,3], such an axial ligation of CuP results in a considerable energy decrease of both the intramolecular chargetransfer (CT) [a2u('rr), d(x 2-y2)] and the ligandfield [d(z2), d(x:-y2)] states. It is the intramolecular CT state of CuP which is generally thought to be responsible for the efficient radiationless excitation deactivation, although this state was not reliably detected spectroscopically, presumably because of its short lifetime [2,3,11,12].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…18 The Raman core size 19,20 and oxidation state marker bands 20 -23 were found to be good indicators of the electronic state of the central porphyrin core resulting from changes in the state of ligation of the metal. 24,25 We used RR spectroscopy to investigate the metal ion coordination of Cu(II) and Ni(II) ions in some of the Cu and Ni containing heme proteins and thereby correlate the quaternary structural changes associated with different heme environments to the structural heterogeneity within the subunits.…”
Section: Introductionmentioning
confidence: 99%